(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Encryption is the science of concealing data, and because researchers seek to find the best way to hide data fromunauthorized persons to access it, and due to competition in this field, it became necessary to find methods that are difficult forattackers to break the cipher text and know its content, in this research paper a new method was proposed that we called it The “hour glass or sand clock method”, which mainly depends on reducing the size of any message, regardless of its size, to becomeeight-bit size only, in addition to hiding all characters of the messagewith only one character using the principle of arithmeticpower function, and it is the first method that relies in its work on the principle of compressing a complete message to becomeOnlyonecharacter.Whichposesarealchallengeinfrontofallmethodsofbreakingtheciphertextasitwilldealwithonlyonecharacter.By using differentcryptanalysismethods,the proposedmethod’sstrengthandeffectiveness have beenprovenincounteringall types ofattacks.